Characterization and expression analysis of gonad specific igf3 in the medaka ovary - Jiale Xie; Ying Zhong; Yuli Zhao; Wenjie Xie; Jing Guo; Lang Gui; Mingyou Li (Aquaculture and Fisheries, 2022)
The gonad specific expression of insulin-like growth factor 3 (igf3) has suggested an important role of igf3 in fish reproduction. In this study, medaka igf3 was isolated and its expression patterns were compared with igf1, and germ cell gene vasa in adult medaka ovary. Molecular cloning and sequencing showed that the open reading frame (ORF) of medaka igf3 was comprised of 501 nucleotides and encoded 166 amino acid residues. Reverse transcription polymerase chain reaction (RT-PCR) analysis showed that igf3 RNA was specifically expressed in developing embryos and adult gonads of both sexes. Real time quantitative PCR (q-PCR) indicated that igf3 expression was gradually increased during oogenesis, and reached its highest level at stage V. Using Chromogenic and fluorescent in situ hybridization, igf3 was shown to be present in the germ cells of oogonia and in oocytes at stages I-III, as well as abundant in granulosa cells and theca cells of oocytes at stages IV–V. In addition, igf3 and igf1 were expressed mutually in the outer theca cells of stage V oocytes in ovary. Collectively, we demonstrated that gonad specific igf3 could mark medaka ovarian somatic cells and germ cells. These findings highlight the importance of igf3 during ovarian development.